Global research landscape of antiangiogenic therapy for colorectal cancer: a bibliometric analysis of mechanistic insights and clinical advancements - Hou, Ke-Qiang; Wu, Jia-Ming; Chen, Jie (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) is a major global health issue, with over 1.9 million diagnoses yearly and low survival rates in advanced stages. Antiangiogenic therapies (AAT) targeting VEGF and VEGFR have improved outcomes, but resistance mechanisms limit their effectiveness. This study uses bibliometric analysis to link mechanistic insights, such as VEGF splicing variants, with clinical developments, identify global collaboration trends, and propose strategies to reduce resistance and toxicity in treatments.MethodsThis study were used to search the Web of Science databases Core Collection. Studies published in English from 1996 to 2024 were included for analysis. VOSviewer 1.6.20, CiteSpace 6.4.R1, and R 4.4.1 were employed for bibliometric analysis and visualization.ResultsThis bibliometric analysis of 976 publications from 1996 to 2024 shows a 13.65% annual growth rate in CRC antiangiogenic research. China leads with 20.5% of publications, followed by the USA at 15.7% and Japan at 13.1%. Key institutions include Assistance Publique Hôpitaux de Paris, and notable journals are BMC Cancer and Clinical Colorectal Cancer. Keyword evolution reflects a shift from angiogenesis mechanisms to clinical validation of treatments like FOLFIRI with bevacizumab, with a current focus on tumor microenvironment reprogramming and precision survival analytics (2020-2024, burst intensity 6.66). Key milestones include Phase III trials like AVF2107g and ctDNA-guided strategies, along with emerging dual-target inhibitors.ConclusionThis bibliometric analysis reveals a shift from VEGF studies to precision strategies targeting tumor microenvironments, influenced by trials like TRIBE and PARADIGM. Future efforts should focus on multi-omics integration and innovative delivery systems like circadian-targeted nanoparticles for personalized CRC care.